Reinvestigating Entrepreneurship Financing and Poverty Eradication in Nigeria: Any Difference from the Case of Small and Medium Scale Enterprises? Array - Ogunleye, Akin George; Adefisayo, Aderibigbe Ebenizer; Ojo, Lucas B.; Aransiola, Ishola James; Ayomitunde, Aderemi Timothy (The Journal of Accounting and Management, 2020)
This study focuses on examination of the relationship between entrepreneurship financing from the perspective of Small and Medium Scale Enterprises (SMEs) and poverty eradication in Nigeria from 1990 to 2018. Data were collected from the Central Bank of Nigeria Statistical Bulletin and World Development Indicators. Consequently, Autoregressive Distributed Lagged, Bounds test and Error Correction Model techniques were utilized to address the objective of the study. Agriculture and forestry financing did not eradicate poverty in the short run in Nigeria. However, the aggregate commercial banks` SMEs financing, the manufacturing and food processing business financing contributed to poverty eradication in in the short run and long run respectively. But broad money supply contributed to poverty eradication in the short run only. However, this study recommends that any time the goal of the policy makers is to eradicate poverty in Nigeria, entrepreneurship financing with reference to manufacturing and food processing should be embarked upon since it has the capacity to alleviate poverty in the both short run in the country. Similarly, the Central Bank of Nigeria should implement appropriate policies that will increase commercial banks’ lending towards agricultural sub sector.